Determination of Distribution Channel Marketing and Service Innovation Quality in Increasing Consumer Satisfaction - Amiruddin, Yudistira Putra; Modding, Basri (Golden Ratio of Mapping Idea and Literature Format, 2021)
In determining the distribution as an entrepreneur, he must select the distribution channel in his business, and one of them is using the Shopee digital application, creating a page on Facebook, and many other digital accesses that can be used; the aim is to reach more potential customers to see the products being sold, making it easier for prospective customers to see. Customers can contact us online and make transactions easier for customers and entrepreneurs. This research aims to determine the role of distribution channel marketing in increasing customer satisfaction. To find out how service innovation quality increases customer satisfaction. Mapping article use 20 of manuscript form scopus databased index. The proposition in this mapping are H1: Distribution channel marketing has a positive and significant effect on increasing consumer satisfaction. H2: Service innovation quality has a positive and significant effect on increasing customer satisfaction.H3: The distributor channel marketing variable has the most significant influence on increasing consumer satisfaction.